Thyroid-Related Protein Expression in the Human Thymus - Kim, Mi Jeong (Int J Endocrinol, 2017)
Radioiodine whole body scan (WBS), related to sodium iodide symporter (NIS) function, is widely used to detect recurrence/metastasis in postoperative patients with thyroid cancer. However, the normal thymic uptake of radioiodine has occasionally been observed in young patients. We evaluated the expression of thyroid-related genes and proteins in the human thymus. Thymic tissues were obtained from 22 patients with thyroid cancer patients of all ages. The expression of NIS, thyroid-stimulating hormone receptor (TSHR), thyroperoxidase (TPO), and thyroglobulin (Tg) was investigated using immunohistochemistry and quantitative RT-PCR. NIS and TSHR were expressed in 18 (81.8%) and 19 samples (86.4%), respectively, whereas TPO was expressed in five samples (22.7%). Three thyroid-related proteins were localized to Hassall's corpuscles and thymocytes. In contrast, Tg was detected in a single patient (4.5%) localized to vascular endothelial cells. The expression of thyroid-related proteins was not increased in young thymic tissues compared to that in old thymic tissues. In conclusion, the expression of NIS and TSHR was detected in the majority of normal thymus samples, whereas that of TPO was detected less frequently, and that of Tg was detected rarely. The increased thymic uptake of radioiodine in young patients is not due to the increased expression of NIS.